Social Culture Analysis to Compare the Performance of Islamic Bank in Muslim-Majority Countries - Masykuroh, Ely; Sudrajat, Anton; Abdullah, Umar (El-Barka, 2022)
Introduction/Main Objectives: The implementation of Islamic teachings in economic activities cannot be separated from the socio-cultural influence of the local community. Thus, there are possible differences in the expression of Islamic teachings in the economic field, especially the practice of Islamic banks in the Countries of the Middle East region with Islamic banks in countries in the Southeast Asian region. Background Problems: This difference in practice can be caused by differences in the religious behavior of bankers and customers in terms of dimensions of knowledge, passion, practice and religious rituals that are influenced by the socio-cultural of each region so that it has an impact on the performance of each Islamic bank. Novelty: No comparative research on the performance of Islamic banks based on socio-cultural analysis has been found. Research Methods: this study was analyzed the performance of Islamic banks in the Middle East and Southeast Asia regions in 2015-2020 and analyze the relevance between banking performance and socio-culture in both regional groups. The research method used is a mixed quantitative and qualitative research method (Mix Method). Sampling techniques use purposive sampling. The sample in this study was the first Islamic banks established in those countries with the criterion that these banks present annual financial statements that have been audited by independent auditors. The analysis method uses quantitative methods: descriptive statistics, normality test, and Mann-Whitney U test as well as qualitative methods, namely analysis content. Finding/Results: Between Islamic banks in the Middle East and Southeast Asian countries in 2015-2020 there are differences in profitability performance, capital ratios, and liquidity, there is no difference in credit efficiency and effectiveness performance, there is relevance between socio-cultural differences and profitability performance, capital ratios, and liquidity between Islamic banks in the Countries of the Middle East and Southeast Asia regions, and there is no relevance between socio-cultural differences and the performance of credit efficiency and effectiveness between Islamic banks in the countries of the Middle East and Southeast Asia regions.